2019
DOI: 10.1371/journal.pone.0211731
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of electrospun fiber surface nanotopography on neurite outgrowth and branching in neuron cultures

Abstract: Three aligned, electrospun fiber scaffolds with unique surface features were created from poly-L-lactic acid (PLLA). Fibers without surface nanotopography (smooth fibers), fibers with surface divots (shallow pits), and fibers with surface pits (deeper pits) were fabricated, and fiber alignment, diameter, and density were characterized using scanning electron microscopy (SEM). Whole dorsal root ganglia (DRG) were isolated from rats and placed onto uncoated fibers or fibers coated with laminin. On uncoated fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 36 publications
(45 reference statements)
3
53
0
Order By: Relevance
“…The following imaging parameters were used: 5.0 kV-accelerating voltage, 10 mmworking distance, 5.0 nm-spot size, 30 µm-aperture, and ×2,500-magnification. Fiber alignment, diameter, and percent coverage were characterized using FIJI Software as described previously (D'Amato et al, 2019b) to ensure consistency between each fiber group and isolate fingolimod release as the sole variable. A total of 300 fiber angles (100 fiber angles per replicate) and 300 fiber diameters (100 fiber diameters per replicate) were measured for each fiber type, and at least three fields of view were assessed for percent fiber coverage.…”
Section: Scanning Electron Microscopy and Fiber Morphological Charactmentioning
confidence: 99%
See 2 more Smart Citations
“…The following imaging parameters were used: 5.0 kV-accelerating voltage, 10 mmworking distance, 5.0 nm-spot size, 30 µm-aperture, and ×2,500-magnification. Fiber alignment, diameter, and percent coverage were characterized using FIJI Software as described previously (D'Amato et al, 2019b) to ensure consistency between each fiber group and isolate fingolimod release as the sole variable. A total of 300 fiber angles (100 fiber angles per replicate) and 300 fiber diameters (100 fiber diameters per replicate) were measured for each fiber type, and at least three fields of view were assessed for percent fiber coverage.…”
Section: Scanning Electron Microscopy and Fiber Morphological Charactmentioning
confidence: 99%
“…The following procedures were approved by the Institutional Animal Care and Use Committee (IACUC) at Rensselaer Polytechnic Institute. Whole DRG were isolated from 2day-old Sprague Dawley rats (P2) as described previously (D'Amato et al, 2019b). Before culturing the whole DRG, all fiber types were plasmatreated on high for 1 min using an expanded plasma cleaner to improve cell adhesion.…”
Section: Whole Drg Isolation Culture and Percent Adhesion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a higher fiber density implies more topography. Previous studies have demonstrated the effects of topography on axonal growth (Chew et al, 2007;D'Amato et al, 2019;Xie et al, 2014). In this study, we focused on the effect of the amount of space between the fibers, even though the amount of topography may have played an important role in axon guidance and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that maneuvering the surface morphology of electrospun fibers (eg, crimped fibers, wrinkled fibers, porous fibers, grooved fibers, cactus‐like fibers, tree‐like fibers, ribbon fibers, rough fibers, beaded fibers, and butterfly wings fibers) leads to enhancing or changing their properties …”
Section: Introductionmentioning
confidence: 99%